Sổ tay hướng dẫn phòng bệnh ký sinh trùng truyền lây từ lợn sang người và cải thiện thực hành vệ sinh trong chuỗi sản xuất thịt lợn bản địa - International Livestock Research Institute (International Livestock Research Institute, 2021)
The purpose of this handbook is to increase awareness and knowledge on PPBD’s of pork value chain actors including farmers, butchers, retailers and consumers with emphasis on Ban or indigenous pigs’ production in local communities as well as to advise on good hygiene practices to reduce the risk of food-borne diseases. The handbook is seen as an additional practical guide for safer Ban pig production but does not replace existing regulations.